Impact of AFTA on Malaysian Trade Flows: An Empirical Analysis Based on Gravity Model - Goh, Lim Thye (2002)
The main purpose of this study is to empirically examine the trade linkages among ASEAN countries with existing of AFTA using gravity model. To achieve the objectives, the multivariate relationship between the trade flows and the four macroeconomic variables are tested through multivariate Johansen cointegration tests and multivariate Granger causality tests based on VECM and also the Impulse Response Function are applied to capture the dynamic linkages among the macroeconomic variables. Annual data covering the period from 1965 to 2000 was utilized in this study. The ASEAN countries concerned in this study are Indonesia, Malaysia, Philippines, Singapore and Thailand. The empirical results of this study indicates that the macroeconomics variables as concerned by Erkkila-Widgren and Meronen gravity model are found to be significantly cointegrated for both export flows and import flows of Malaysia within the ASEAN countries in long run. However, in short run the evidences of the Granger causality between trade flows and macroeconomic variable IS only significant determinant in certain countries as proven by multivariate Granger causality test based on VECM Under the impulse response function framework, dynamic linkages between Malaysian trade flows and macroeconomic variables are identified. The results indicate that APTA and population are positively cointegrated with Malaysian trade flows, whereas GDP per capital of the observed ASEAN countries and distance are negatively co integrated with Malaysia trade flows. This study thus implies that an efficient trade agreement in ASEAN region will promote a better performance of a country's trade flows. This in turn will create more employment opportunities and stimulate economic growth.